Nursing Care for Dengue Hemorrhagic Fever Patients with Deep Breath Relaxation Intervention to Reduce Pain - Tita Saskia Asmoro; Muhamad Zulfatul A'la; Mulia Hakam; Heri Siswanto (KHD Production, 2025)
Dengue fever or hemorrhagic fever is an acute infectious disease that can be transmitted by the Aedes aegypti mosquito. The virus carried by the Aedes aegypti mosquito will attack cells in the liver, disrupting liver function and causing swelling and bleeding. Symptoms that can occur are high fever, muscle and joint pain, and rash. One of the nonpharmacological therapies is deep breath relaxation therapy to reduce pain. This study aims to analyze deep breath relaxation techniques to reduce pain. This research design used a case report approach. The pain can decrease after being given deep breath relaxation therapy for 3 days. On the first day, on a scale of 7, it decreased to a scale of 2 on the third day of hospitalization. Applying deep breath relaxation techniques can help reduce pain intensity by relaxing skeletal muscles that experience spasms due to increased prostaglandins, so that vasodilation of blood vessels will increase blood flow that is spasmed and ischemic. This technique can help a person or patient control themselves when feeling emotional discomfort, physical stress, or pain. Deep breath relaxation techniques can be given to patients who experience pain as a nonpharmacological therapy. The application of this relaxation technique is proven to reduce pain intensity.